Children with Severe Obesity in Family‐Based Obesity Treatment Compared with Other Participants: Conclusions Depend on Metrics. Issue 2 (24th January 2021) - Hayes, Jacqueline F.; Fowler, Lauren A.; Balantekin, Katherine N.; Saelens, Brian E.; Stein, Richard I.; Perri, Michael G.; Welch, R. Robinson; Epstein, Leonard H.; Wilfley, Denise E.
Abstract : Objective: This study compares children with severe obesity and children with mild obesity/overweight participating in family‐based obesity treatment (FBT) on change in (1) relative weight and adiposity and (2) psychosocial distress. Methods: Children 7 to 11 years old ( N = 241) and their parents participated in 12 months of behavioral treatment (FBT + maintenance treatment) and completed anthropometric, adiposity, and psychosocial assessments (psychiatric disorder symptomology, quality of life). Severe obesity was defined as a baseline BMI ≥ 120% of the 95th percentile ( N = 105). Results: At 12 months, 40% of children with baseline severe obesity no longer had severe obesity. Percent overweight and fat mass index measurements showed similar magnitudes of change among children with severe obesity and children with mild obesity/overweight, whereas BMI z score and percent body fat change was lower in the group with severe obesity. Youth with severe obesity were higher on some measures of psychosocial distress at baseline but generally experienced improvements similar to children with mild obesity/overweight. Conclusions: FBT with maintenance treatment is beneficial for children with severe obesity and is recommended for use prior to more invasive treatments in severe pediatric obesity. Future studies should assess the necessity of additional treatment, as children with severe obesity still have high relative weights post intervention.